A Fast Atmospheric Sound Propagation Model for Aircraft Noise Prediction. Issue 5 (October 2014) - Tuinstra, Marthijn
The effect of the atmosphere on sound propagation can impact the perceived noise on the ground significantly and therefore needs to be accounted for in aircraft noise modelling. However, to be practical, propagation modelling cannot impose a limitation on calculation time. The aim is therefore to design a robust and computationally lean atmospheric propagation model for the prediction of aircraft noise. Foreseen applications are the evaluation of en-route noise, noise optimisation studies and the evaluation of noise in airport scenarios. To achieve a computationally low demanding algorithm an analytical approach is pursued. When the wave front orientation is approximated to be perpendicular to the ray path, it follows from the Eikonal equation that a ray obeys to an adapted form of Snell's law. If the atmosphere is then discretized in layers of linearly varying sound speed and wind velocity, it allows the ray path and ray properties to be expressed analytically within a layer. Cross-validation against two independently developed ray tracing routines has shown the validity of the selected modelling approach. In conclusion, a robust and computationally low demanding method has been developed for atmospheric sound propagation that can be incorporated in aircraft noise modelling.